EXPERIMENTAL TESTS OF GARNET PERIDOTITE OXYGEN BAROMETRY - Gudmundsson, G; Wood, B (1995)
We have performed experiments aimed at testing the calibration of oxygen barometers for the garnet peridotite [garnet (Gt)-olivine (Ol)-orthopyroxene (Opx)] phase assemblage. These involved equilibrating a thin layer of garnet sandwiched between layers of olivine and orthopyroxene at 1300°C and 23-35 kbar for 1-7 days. Oxygen fugacity was controlled (but not buffered) by using inner capsules of Fe-Pt alloy or graphitc or molybdenum sealed in welded Pt outer capsules. Post-experiment measurement of fO2 was made by determining the compositions of Pt-Fe alloy sensors at the interface between garnet and olivine + orthopyroxene layers. The composition of alloy in equilibrium with olivine + orthopyroxene was approached from Fe-oversaturated and Fe-undersaturated conditions in the same experiment with, in general, excellent convergence. Product phase compositions were determined by electron microprobe and a piece of the garnet layer saved for 57Fe Mössbauer spectroscopy. The latter gave the Fe3+ content of the garnet at the measured P-T-fO2 conditions. Approach to equilibrium was checked by observed shifts in Fe3+ content and by the approach of garnet-olivine Fe-Mg partitioning to the expected value. The compositions of the phases were combined with mixing properties and thermodynamic data to calculate an apparent fO2 from two possible garnet oxybarometers:- Mathematical expression and Mathematical expression Comparison of calculated fO2s with those measured by the Pt-Fe sensors demonstrated that either barometer gives the correct answer within the expected uncertainty. Data from the first (Luth et al. 1990) has an uncertainty of about 1.6 log fO2 units, however, while that from equilibrium (2) (Woodland and O'Neill 1993) has an error of +/- 0.6 log units, comparable to that of the spinel peridotite oxybarometer. We therefore conclude that equilibrium (2) may be used to calculate the fO2 recorded by garnet peridotites with an uncertainty of about +/- 0.6 log units, providing the potential to probe the oxidation environment of the deep continental lithosphere. Preliminary application based on data from Luth et al. (1990) indicates that garnet peridotite xenoliths from Southern Africa record oxygen fugacities about 3.0 log units below the FMQ (fayalite-magnetite-quartz) buffer. These are substantially more reducing conditions than those recorded by continental spinel lherzolites which typically give oxygen fugacities close to FMQ (Wood et al. 1990). © 1995 Springer-Verlag.